Use of modified deep eutectic solvent as an additional chemical in a flexible conductive natural rubber sensor for motion analysis - Boripat Sripornsawat; Antonia Georgopoulou; Sarttrawut Tulaphol; Anoma Thitithammawong; Jobish Johns; Yeampon Nakaramontri; Frank Clemens (eXPRESS Polymer Letters)
The strain sensors based on conductive natural rubber (NR) composite, filled with carbon nanotubes (CNT) and conductive carbon black (CCB), are developed due to their superior elasticity and sensitivity. To encourage electron tunneling, ionic pathway for electron moving was achieved by modified deep eutectic solvent (mDES) synthesized in-house. It was found that the incorporation of mDES impacts the curing, mechanical and electrical properties of the composites due to the interconnected CNT/CCB-mDES networks. It is demonstrated that the electrical signal sensation of conductive NR composite was improved by adding mDES, and the inconsistent sensor behavior under cyclic and quasi-static loadings was eliminated. The mDES not only improves the movement of electrons, but it also promotes the crosslinking of NR molecules without adding ZnO. In addition, for analyzing the object motion, the piezoresistive rubber sensors were tested on a soft printing structure through the cyclic motion analysis of a soft tendon-based actuator. The obtained electrical signals showed the smooth signal with noise and un-prediction electrical peaks after the combination of the mDES into the conductive NR composites. This clarifies the flexible movement of the CNT/CCB structure into the NR matrix following the specific designed objects’ motion. The present work indicates the different core novel technologies based on the use of mDES in the conductive composites matching with the acceptable electrical signal for applying as the promising motion sensor materials for soft structures.